2013
DOI: 10.7763/ijssh.2013.v3.211
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Leadership Practices, Organizational Climate and Its Effect towards Innovative Work Behaviour in R&D

Abstract: Abstract-Achieving innovative organization has been the utmost agenda in every business operations recently. Thus, there is a need for a greater understanding of the leadership and organizational climate effect towards innovative work behaviour in work settings, particularly in R&D which involves creativity and innovation activities. The aim of this paper is to explore the relationship between leadership practice and organizational climate effect and its mediating effect towards innovative work behaviour. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
3
15
0
1
Order By: Relevance
“…Innovative Work Behavior at Critical Care Units This reflects what was emphasized by Noor and Dzulkifli (2013) who conducted study about ''assessing leadership practices, organizational climate and its effect towards innovative work behavior in R&D''. They found that study participants prioritized making difference in work as an objective for their life and they seek opportunities to it [12]. This is due to the creativity come up with new ideas primarily depends on individuals and partly on the management of an organization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Innovative Work Behavior at Critical Care Units This reflects what was emphasized by Noor and Dzulkifli (2013) who conducted study about ''assessing leadership practices, organizational climate and its effect towards innovative work behavior in R&D''. They found that study participants prioritized making difference in work as an objective for their life and they seek opportunities to it [12]. This is due to the creativity come up with new ideas primarily depends on individuals and partly on the management of an organization.…”
Section: Discussionmentioning
confidence: 99%
“…According to Noor & Dzulkifli (2013) and Chombunchoo (2016) innovative work behavior include three stages: idea generation, coalition building and implementation. In the idea generation, innovation is started by problem identification, defining problem and finding a solution to solve the problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, R. Shanker, R. Bhanugopan, van der Heijden, M. Farrell [16] identified that OC variables such as organisational support, management support, support by team member and challenging work have strong impact on individual innovation and creativity. So, to boost creativity and innovation of among the workforce, organisations should create a work environment with supportive features and reward strategy [48].…”
Section: Organisational Climatementioning
confidence: 99%
“…One of the factors that influence innovative behavior is the organizational climate. Research conducted by Sari and Ulfa (2013), and Noor and Dzulkifli (2013) revealed that organizational climate has a positive effect on innovative work behavior, meaning that the better organizational climate perceived by employees the higher the innovative behavior in the work of the employee. According to Stringer (2002) there are six organizational climate components:…”
Section: Introductionmentioning
confidence: 99%